Integrasi Analisis Log dan Dutta Crossplot untuk Identifikasi Zona Overpressure dan Potensi Hidrokarbon di Formasi Kujung dan Ngimbang - Vina Wiryadinata; Abdul Haris (Jurnal Penelitian Pendidikan IPA, 2025)
The North East Java Basin is one of the prospective hydrocarbon areas in Indonesia with the Kujung and Ngimbang Formations as the main intervals of the petroleum system. This study aims to identify the mechanism of overpressure formation and reservoir potential based on well log data analysis. The methods used include interpretation of Gamma Ray (GR), Resistivity (ILD), Neutron porosity (NPHI), and Bulk Density (RHOB) logs, as well as pore pressure estimation using the Eaton method. The analysis results indicate that the Kujung Formation has two prospective zones at depths of 4200–4800 ft and 7500–8500 ft indicating a gas-bearing carbonate reservoir, while the Ngimbang Formation is dominated by shale and dense carbonate that function as cap and source rocks. The beginning of the overpressure zone was detected at a depth of approximately 4400 ft, characterized by anomalies in the NPHI, RHOB, and Δt logs indicating undercompaction. Dutta crossplot analysis (DT–RHOB) confirmed the dominance of smectite minerals indicating that the overpressure was formed due to a loading mechanism. Thus, the Kujung Formation acts as a porous reservoir zone, while the Ngimbang Formation functions as a cap rock in the North East Java Basin petroleum system.